2011
DOI: 10.4007/annals.2011.174.2.6
|View full text |Cite
|
Sign up to set email alerts
|

Arithmetic groups have rational representation growth

Abstract: Let Γ be an arithmetic lattice in a semisimple algebraic group over a number field. We show that if Γ has the congruence subgroup property, then the number of n-dimensional irreducible representations of Γ grows like n α , where α is a rational number.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
63
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 31 publications
(66 citation statements)
references
References 19 publications
2
63
0
1
Order By: Relevance
“…In the same way, it refines the variant of this conjecture that was proved in [6,Theorem 1.2]. Indeed, Corollary B asserts that, for the relevant arithmetic groups Γ, not only the degree of representation growth but also the order of the pole of the meromorphically continued function at s = α(Γ), and thus the exponent of the log-N -term in (2), are invariants of the type A 2 . Likewise meromorphic continuation can be achieved uniformly in a strip of width at least 1/6.…”
Section: Introduction and Discussion Of Main Resultssupporting
confidence: 71%
See 1 more Smart Citation
“…In the same way, it refines the variant of this conjecture that was proved in [6,Theorem 1.2]. Indeed, Corollary B asserts that, for the relevant arithmetic groups Γ, not only the degree of representation growth but also the order of the pole of the meromorphically continued function at s = α(Γ), and thus the exponent of the log-N -term in (2), are invariants of the type A 2 . Likewise meromorphic continuation can be achieved uniformly in a strip of width at least 1/6.…”
Section: Introduction and Discussion Of Main Resultssupporting
confidence: 71%
“…Otherwise the abscissa of convergence α(G) satisfies α(G) = lim sup N →∞ log (R N (G)) log N and thus gives the degree of polynomial growth. For a range of results on representation growth and zeta functions of arithmetic and profinite groups see, for instance, [41,2,30,38,51,1]. The current paper forms part of a series of papers on representation growth; see [3,4,5,6].…”
Section: Introduction and Discussion Of Main Resultsmentioning
confidence: 99%
“…Hence (II) follows.It is clear that δ(G) := max{a(G)−δ 1 , d 3 } is independent of the number field K and the zeta functionζ G(O) (s) may be continued to {s ∈ C | Re(s) > a(G) − δ(G)}. The order β(G) of the pole of p ∈Q V −1 p (s) at s = a(G)is clearly an invariant of G, which proves(2). The statement about the holomorphy of the continued function follows from the fact that the meromorphic continuation was achieved by writing ζG(O) (s) as a product of translates of Artin L-functions (implicit in the proof of Proposition 4.3) and a Dirichlet series convergent on {s ∈ C | Re(s) > a(G) − δ(G)}; cf.…”
mentioning
confidence: 71%
“…Most general results about the analytic properties of Euler products of the nonarchimedean factors are based on suitable approximations of the individual Euler factors. Using such techniques, it was shown that the abscissa of convergence of ζ Γ (s) is a rational number ( [2]) which only depends on the absolute root system of the algebraic group G; cf. [4].…”
Section: Representation Growth Of 'Semisimple' Arithmetic Groupsmentioning
confidence: 99%
See 1 more Smart Citation